Rancang Bangun Prototype Single Electrode EEG Berbasis Arduino Uno - Handayani, Nita; Kurniawan, Ade; Handayani, Yulia Savitri (Sunan Kalijaga Journal of Physics, 2021)
Research on electroencephalography (EEG) design as a detector of brain signal activity in the frontal lobe based on Arduino Uno has been completed. EEG is a tool used to record electrical activity in the human brain. This research aims to make a non-clinical EEG device that is portable and low-cost. The research procedure is divided into three stages. The first stage is to design an EEG system using the Eagle application. The second stage is to create an EEG system which consists of the primary circuit of the EEG system, power supply, Arduino Uno, and two electrodes. The third stage is testing the EEG system, which includes testing the instrumentation amplifier, low pass filter, power supply, Arduino ADC consistency, and initial testing of EEG performance to record brain signals. The instrumentation gain is 51 times based on the test with an average accuracy rate of 99.09%. Meanwhile, the cut-off frequency obtained is 70 Hz. The comparison between brain signal measurements using a single electrode prototype EEG and standard EEG Emotiv Epoc with electrode placement at points Fp1 and A2 (ground) show almost the same pattern. So it can be said that the single EEG system created has been successfully used to record brain activity in the frontal lobe area.